Low Frequency Radio Pulses Produced by Terrestrial Gamma‐Ray Flashes. Issue 12 (19th June 2019) - Pu, Yunjiao; Cummer, Steven A.; Lyu, Fanchao; Briggs, Michael; Mailyan, Bagrat; Stanbro, Matthew; Roberts, Oliver
Abstract: Do terrestrial gamma‐ray flashes (TGFs) produce their own radio signatures? To explore this question, we analyze TGF data from the Fermi Gamma‐ray Burst Monitor, independent lightning geolocation data from the National Lightning Detection Network, and low‐frequency (LF) magnetic field waveforms, to determine the relationship between TGF generation and LF waveforms. LF waveforms associated with six TGFs are found to contain a clear and isolated slow pulse ( 80‐μs duration) within a sequence of multiple fast pulses (<10‐μs risetime). We find that the slow LF pulse is produced simultaneously with the observed gamma rays, with an uncertainty as small as 7 μs. Simultaneity implies a consistent TGF source altitude range of approximately 10–15 km, which is consistent with previous estimates. These findings provide important evidence that the slow LF pulse, when observed, is associated with TGF production and perhaps produced by the electron acceleration itself. Key Points: Approximately 10% of TGFs are simultaneous with a distinct and isolated slow low frequency radio pulse Simultaneity implies that a TGF source altitude range of 10‐15 km is consistent with the analyzed examples The consistency of the TGF and radio time scales indicate that the radio pulse is produced directly by the electron acceleration in the TGF production process